1960
DOI: 10.1002/j.1551-8833.1960.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Carbonate Alkalinity in Natural Waters

Abstract: This article discusses the Larson and Henley method for determining low alkalinities in rain water. The method increases the accuracy of the determination of carbonate alkalinity as it eliminates the error due to variation of true equivalence point with total alkalinity. The method determines the actual inflection point or equivalence point pH of the titration, and it has been adapted to routine use with no significant decrease in accuracy. The variation of equivalence point of the titration of bicarbonate ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1963
1963
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The alkalinity of water (Alk) was determined by the two-point titration method (to pH 4.5 and 4.2) [4,5] and calculated from the equation Alk = (2 V 4.5 -V 4.2 ) N / V , where V 4.5 and V 4.2 are the volumes of a strong acid consumed for the titration of a sample to pH 4.5 and 4.2, respectively; V is the sample volume; and N is the normality of the acid solution. The amount of organic acid anions was calculated from the ion balance of water,…”
Section: Methodsmentioning
confidence: 99%
“…The alkalinity of water (Alk) was determined by the two-point titration method (to pH 4.5 and 4.2) [4,5] and calculated from the equation Alk = (2 V 4.5 -V 4.2 ) N / V , where V 4.5 and V 4.2 are the volumes of a strong acid consumed for the titration of a sample to pH 4.5 and 4.2, respectively; V is the sample volume; and N is the normality of the acid solution. The amount of organic acid anions was calculated from the ion balance of water,…”
Section: Methodsmentioning
confidence: 99%
“…The highest value of alkalinity ( Fig. 9) was found to be 270 mg/L in Station 7 during the dry season and the lowest value was 78 mg/L in Station 6 during the rainy season due to municipal waste disposal and oil pollution (Thomas and Lynch 1960). This similar observation was made by Mahmood et al (1992) and Paul (1981) who reported that oil pollution in the Karnaphuli River was responsible for increasing the total alkalinity of this river and its tributaries.…”
Section: Seasonal Variation Of Water Parametersmentioning
confidence: 93%
“…A Gran titration is often used to linearize the titration curve using pH endpoints of 4.2 and 3.9, especially in waters of low alkalinity (American Public Health Association, 2005;Thomas and Lynch, 1960).…”
Section: Ph-alkalinity Titrationsmentioning
confidence: 99%
“…Temperature and pH were measured in-situ at the same location where the CO 2 water samples were collected. Alkalinity was measured using a two-endpoint method (pH 4.2 and 3.9) and calculated using a Gran function (Thomas and Lynch, 1960). A digital titrator (Hach Company, Loveland, CO) was used to titrate samples using 1.6 N sulfuric acid.…”
Section: Field and Laboratory Analysismentioning
confidence: 99%